Genotype–phenotype correlation and functional studies in patients with cystic fibrosis bearing CFTR complex alleles. Issue 4 (13th October 2016) - Terlizzi, Vito; Castaldo, Giuseppe; Salvatore, Donatello; Lucarelli, Marco; Raia, Valeria; Angioni, Adriano; Carnovale, Vincenzo; Cirilli, Natalia; Casciaro, Rosaria; Colombo, Carla; Di Lullo, Antonella Miriam; Elce, Ausilia; et al.
Abstract : Background: The effect of complex alleles in cystic fibrosis (CF) is poorly defined for the lack of functional studies. Objectives: To describe the genotype–phenotype correlation and the results of either in vitro and ex vivo studies performed on nasal epithelial cells (NEC) in a cohort of patients with CF carrying cystic fibrosis transmembrane conductance regulator ( CFTR ) complex alleles. Methods: We studied 70 homozygous, compound heterozygous or heterozygous for CFTR mutations: p.[Arg74Trp;Val201Met;Asp1270Asn], n=8; p.[Ile148Thr;Ile1023_Val1024del], n=5; p.[Arg117Leu;Leu997Phe], n=6; c.[1210-34TG[12];1210-12T[5];2930C>T], n=3; p.[Arg74Trp;Asp1270Asn], n=4; p.Asp1270Asn, n=2; p.Ile148Thr, n=6; p.Leu997Phe, n=36. In 39 patients, we analysed the CFTR gating activity on NEC in comparison with patients with CF (n=8) and carriers (n=4). Finally, we analysed in vitro the p.[Arg74Trp;Val201Met;Asp1270Asn] complex allele. Results: The p.[Ile148Thr;Ile1023_Val1024del] caused severe CF in five compound heterozygous with a class I–II mutation. Their CFTR activity on NEC was comparable with patients with two class I–II mutations (mean 7.3% vs 6.9%). The p.[Arg74Trp;Asp1270Asn] and the p.Asp1270Asn have scarce functional effects, while p.[Arg74Trp;Val201Met;Asp1270Asn] caused mild CF in four of five subjects carrying a class I–II mutation in trans, or CFTR-related disorders (CFTR-RD) in three having in trans a class IV–V mutation. The p.[Arg74Trp;Val201Met;Asp1270Asn] causes significantly (p<0.001) higher CFTR activity compared with compound heterozygous for class I–II mutations. Furthermore, five of six compounds heterozygous with the p.[Arg117Leu;Leu997Phe] had mild CF, whereas the p.Leu997Phe, in trans with a class I–II CFTR mutation, caused CFTR-RD or a healthy status (CFTR activity: 21.3–36.9%). Finally, compounds heterozygous for the c.[1210-34TG[12];1210-12T[5];2930C>T] and a class I–II mutation had mild CF or CFTR-RD (gating activity: 18.5–19.0%). Conclusions: The effect of complex alleles partially depends on the mutation in trans . Although larger studies are necessary, the CFTR activity on NEC is a rapid contributory tool to classify patients with CFTR dysfunction.